BASIC ACTUAL AND EFFECTIVENESS OF LEADERSHIP STYLES OF CONSTRUCTION PROJECT MANAGERS IN SURABAYA - Andi Andi; Wahyu Kurniawan Santoso; Ronald Chandra Tali (Civil Engineering Dimension, 2004)
Leading is one of the most important facets in managing construction projects, and behaving as an effective leader is a vital project manager’s responsibility to ensure that work efforts of other persons are directed toward the accomplishment of organizational objectives. This paper aims to determine basic and actual leadership styles of construction project managers in Surabaya. The effectiveness of the actual leadership style is also examined. To accomplish the objective, the paper first briefly reviews the ways in which leadership is approached. Data were then collected through an empirical survey to 46 project managers, taking Fiedler and Hersey-Blanchard’s models as the point of departure. The results indicate that the basic leadership of project managers in Surabaya falls slightly on task-oriented behavior. Meanwhile selling is the most common style used as actual leadership in practice. The paper discusses the effectiveness of the styles adopted and situational variables affecting.